Cover Image. (21st April 2020) - Kim, Jin Woo; Park, Jong Ho; Muthukumar, Thangavelu; Shin, Eun Yeong; Shin, Myeong Eun; Song, Jeong Eun; Khang, Gilson
Abstract : The cover image is based on the Original Article Accelerating bone defects healing in calvarial defect model using 3D cultured bone marrow‐derived mesenchymal stem cells on demineralized bone particle scaffold . by GILSON KHANG, Eun Yeong Shin, Park Jong Ho et al., https://doi.org/10.1002/term.3020. .